The Significance of Sanad ‘Ālī in Ninth-Century Hijri Hadith Transmission: An Analysis of Ibn Ḥajar Al-’Asqalani’s Thought - Muhammad Syaikhur Ridho; Fajar Syarif Mubarok; Indika Ilwan Wahilmi (ISTIFHAM, 2026)
Scholars of hadith from the Salaf period generally preferred hadiths with a minimal number of narrators in the isnad, known as 'ālī hadiths. This preference was partly due to the reduction of potential distortion in transmission associated with fewer narrators. It is evident that the 'ālī isnad was regarded as significant by hadith scholars during the early period. However, the importance of the 'ālī isnad following the codification of hadith has not been sufficiently examined. This study aims to ascertain whether the 'ālī isnad retained any significance after the period of hadith codification, with particular attention to the ninth century. Focusing on the work of Ibn Hajar al-Ahādīth al-‘Ashrah al-‘Ushāriyyah, this research endeavors to demonstrate the high status attributed to the chain of narration within that text, as asserted by the author. By tracing contemporary reports (tābi’ and shāhid) related to the hadiths included by Ibn Hajar, it is possible to reconstruct the attitudes of scholars in the ninth century towards high chains (‘ālī). Consequently, this study aims to reveal the perception of high chains during that period, both theoretically and practically. Furthermore, the research indicates that the transmission of hadiths persisted even when not all were documented in written sources, in contrast to practices observed in earlier periods